Intelligent Screening of Prostate Cancer Individuals Using an Enzyme‐Assisted Multicolor Visualization Platform - Ruomei Teng; Ming Li; Zikang Chen; Jianli Lin; Yuhan Zhang; Hang Li; Zejun Yan; Dingyuan Zhang; Caiping Ding; Youju Huang (Advanced Science)
Abstract Rapid and intelligent identification of prostate cancer (PCa) is critical for early diagnosis. Herein, a convenient, reliable, and intelligent strategy is proposed to screen PCa individuals through indirectly quantifying sarcosine (Sar), an early indicator of PCa, in clinical urine samples. Success is achieved by integrating sarcosine oxidase (SOX) as a specific recognition unit; nanozyme‐assisted multicolor intelligent visualization platform as a signal reporter. With the Fe‐MOFs and peroxidase, the synergetic action of SOX and response gold nanorods (Au NRs) is controlled etched to exhibit a multicolored signal. The sensor exhibits excellent linearity with Sar within 1–60 × 10−6 m, boasting a remarkable detection limit of 0.12 × 10−6 m. The RGB value of the display color can be directly extracted using a mobile phone camera. PCa diagnosis can be swiftly made (within 15 min) and directly by identifying two RGB colors (R < 175 or B > 135). The enzyme‐assisted multicolor intelligent visualization platform is adept at detecting minute differences in Sar concentration in urine samples between PCa patients and healthy individuals. The concept of enzyme‐assisted multicolor sensing can be further expanded by modifying the type of immobilized enzymes, providing a valuable guideline for the rational design of multiple probes to measure specific biomarkers in biological samples.